TEACHING ENGLISH TO YOUNG LEARNERS AS A SECOND LANGUAGE WITH INTERACTIVE TECHNIQUES - Madina Togayeva (Journal of new century innovations, 2023)
In today’s world, knowing a second language has been not only a necessity but also a requirement for people in their professional success and career. In order to gain such kind of skill , it is advised to begin it from an early age.